Development and economic trends in anticancer drugs licensed in the UK from 2015 to 2019. Issue 2 (February 2021) - Lythgoe, Mark P.; Krell, Jonathan; Mahmoud, Sarah; Mills, Emily C.; Vasudevan, Aishwarya; Savage, Philip
Highlights: Unprecedented numbers of new anti-cancer drug licensed during this period. Transition away from cytotoxic chemotherapy to targeted therapies. Newer anti-cancer therapies have longer average median durations of treatment. Newer drugs are associated with a significantly higher financial burden. Abstract : Analysis of new anticancer drugs licensed in the UK found that 44 new therapies were approved from 2015 to 2019. No other 5-year period has produced as many new therapies. Most new drugs are kinase inhibitors (KIs, N = 18) and monoclonal antibodies (mAbs, N = 16) with only one classical cytotoxic chemotherapy (CC) licensed. The average median treatment duration has risen by 55 days to 318 days (263 days in 2010–2014). Drug costs have escalated; an average treatment course now costs £62 343, compared to £35 383 in 2010–2014. New drugs are delivering significant clinical benefits with longer treatment durations. However, the financial burden is greater, heralding economic challenges for healthcare providers.